Performance and Heterophil to Lymphocyte (H/L) Ratio Profile of Broiler Chickens Subjected to Feeding Time Restriction - Azis, A. (International Journal of Poultry Science, 2012)
The objective of the current study was to evaluate the effect of feeding time restriction in alternate day on performance and Heterophil to Lymphocyte (H/L) ratios as indices stress of broiler chickens. A total 180 seven day-old unsexed broiler chicks were randomly allocated to three treatments: chicks fed ad libitum (P-0); chicks had free access to feed from 07:00 to 09:00, 12:00 to 13:00 and 17:00 to 18:00 (P-1) and from 07:00 to 09:00 and 17:00 to 18:00 (P-2). The feeding time restriction was given at 7, 9, 11, 13, 15, 17, 19 and 21 days of age and chicks was access feed ad libitum on alternate days (8, 10, 12, 14, 16, 18 and 20 days of age). The chicks were fed ad libitum during 22 to 42 days of age. Body weight gain, feed intake and feed conversion ratio in feed restricted broilers were lower (p